Simplified approach to predict the flexural strength of self-centering masonry walls. (1st July 2017) - Hassanli, Reza; ElGawady, Mohamed A.; Mills, Julie E.
Highlights: The behavior of unbonded post-tensioned masonry walls (PT-MWs) is studied. The accuracy of different flexural expressions is investigated. A simplified design approach is proposed to predict the flexural strength PT-MWs. The procedure was validated against experimental and finite element model results. Abstract: This paper develops a simplified design approach to predict the flexural strength of unbonded post-tensioned masonry walls. The accuracy of different flexural expressions was investigated according to experimental and finite element modelling results. Using an analytical model and considering the stress-strain relationships for unconfined and confined masonry, force displacement curves were developed for eleven tested walls, with and without confinement plates. The developed force–displacement procedure was able to predict the lateral strength, stiffness and post-peak degradation of the behavior of the tested walls. Using a similar analytical procedure, a parametric study was performed to obtain the force-displacement response of walls with different features and to investigate the effect of different parameters including axial stress ratio, length, height and thickness of the wall, on the compression zone length. Multivariate regression analysis was performed to develop an empirical equation to estimate the compression zone length in unbonded post-tensioned walls. According to the results, the wall length and axial stress ratio were found to be the most significant factors affecting the compression zone length. Depending on the configuration of the wall, the compression zone length varied between 6.7% to 28% of the wall length. The proposed equation for compression zone length was then incorporated into the flexural analysis of post-tensioned masonry walls and validated against experimental results and finite element results. Comparing the prediction from Masonry Standards Joint Committee, MSJC (2013), and the proposed method reveals that ignoring the elongation of PT bars in strength prediction resulted in a considerable underestimation of the strength. Using the non-iterative proposed approach significantly improved the prediction.